Collagen Extraction From Bigeye Tuna (Thunnus obesus) Bone Byproduct: Process Modeling and Technoeconomic Assessment Using SuperPro Designer - Abyan Shiddiiq; Elly Septia Yulianti; Misri Gozan; Siti Fauziyah Rahman (Journal of Engineering)
This study evaluates the potential of utilizing tuna bone byproducts for acid-soluble collagen (ASC) extraction in Indonesia, targeting the biomedical industry’s growing collagen demand. Through the SuperPro Designer Simulator, the research assesses the economic feasibility of four varying input capacities (50, 100, 500, and 1000 kg). The simulation reveals that the most economical production process occurs with 1000 kg of raw materials, yielding a net present value (NPV) of $3,848,000, an internal rate of return (IRR) of 35.55%, and a payback period (PBP) of 2.16 years. The 1000-kg scenario emerged as the most economical input capacity due to its ability to adequately cover the substantial initial investment required. This outcome highlights the importance of scale efficiencies and operational optimizations in enhancing profitability, suggesting that large-scale operations are essential for justifying the significant capital expenditures involved. This project faces significant challenges in the limited availability of raw materials and the current extraction method’s efficiency, which could hinder the feasibility of scaling up production. This study identifies strategic solutions to these challenges by reducing investment through contract and shared manufacturing systems to lower upfront costs and improve the extraction process for higher efficiency and yield. These measures aim to address material scarcity and enhance production method efficacy, making the project more sustainable and economically viable. This study advocates further research and development to optimize the tuna bone byproduct extraction process as a solution to establish a competitive approach for collagen production within Indonesia’s biodiversity-rich maritime sector.